A 14C and 15N study of the effects of ammonium or nitrate nutrition on carbon allocation in Triticum aestivum L. and Zea mays L - Van der Leij, Martina (Department of Biological Sciences, 2016)
The poor response of some plant species, e.g. wheat, to ammonium nutrition has been attributed to a diversion of carbon allocation from structural material for root extension to functions associated with the assimilation and translocation of ammonium in the root. The aim of this research was to investigate carbon allocation in response to ammonium or nitrate nutrition in wheat, an ammonium intolerant species, and maize, which exhibits ammonium tolerance. Experiments were carried out at 4mM and 12mM nitrogen feeding levels in sand and hydroponic culture respectively. pH of growth media was maintained at 6.0 to 6.5. Measurements made included shoot : root ratios, photosynthetic and root respiratory rates, plant water content, xylem sap analysis, and ¹⁴C and ¹⁵N allocation to soluble and bound nitrogen compounds, and soluble, storage and structural carbohydrates. Stunted root growth occurred in ammonium-fed wheat, which was exacerbated by increasing the NH4 concentration. No difference in growth response was evident between ammonium- and nitrate-fed maize. Photosynthetic rates of ammonium- and nitrate-fed plants within both species were similar but maize showed a 3-fold higher photosynthetic rate than wheat. Root respiration of ammonium- and nitrate-fed wheat was similar, while nitrate-fed maize appeared to have a higher root respiratory rate than ammonium-fed maize. Xylem sap analysis showed that for both species, ammonium-fed plants translocated more amino compounds and more carbon to the shoots than nitrate-fed plants, although maize appeared to have a more rapid translocation-rate than wheat. ¹⁴C allocation to nitrogenous compounds in roots of ammonium-fed plants was greater than that in nitrate-fed counterparts for both species. In wheat this increase appeared to be accommodated by a larger initial diversion of ¹⁴C to the root. In maize, reserve carbon in the root appeared to accommodate this increase. A reduction in ¹⁴C allocation to structural material in ammonium-fed plants compared to nitrate-fed counterparts was not evident in either species. ¹⁵N tracing in maize showed that significantly more nitrogen was taken up by ammonium-fed plants in comparison to nitrate-fed plants. The difference in total N between plants fed ammonium or nitrate was, however, not nearly as pronounced, suggesting that ammonium may be cycled out of the plant again. The response of wheat and maize to ammonium or nitrate nutrition is discussed independently, and suggestions for further research are made.